A comparative study of the leadership skills of the millennial male and millennial female managerial leaders in the Indian service sector. (26th February 2021) - ; Kumar, Pranab
The millennial generation forms a considerable percentage of the workforce worldwide. Hence, it is important for organisations to understand the values and perspectives that they bring to work. With millennials already in leadership positions in many organisations worldwide and many of them soon going to assume leadership roles, it is crucial to understand their way of leading people. Millennials were born in a time when more and more women started to join workforce. The present study tries to bring out observable differences in the leadership skills of male and female managerial leaders who belong to the Indian service sector. Practical implications related to gender diversity, inclusion and the glass ceiling that women in leadership roles face have also been discussed.